Synthesis of Humic Acid from UTP Vermicompost at Different C/N Ratio for Electricity Generation - Lim, Wen Khai (Universiti Teknologi PETRONAS, 2016)
Universiti Teknologi PETRONAS (UTP) is a private university that occupied 400 hectares of compound where most are covered in greens. The green wastes such as fallen leaves and vegetable scraps that are generated daily in UTP are high in volume. Those green wastes not only can be utilised to produce UTP own fertilizer but also reduction of cost to maintain landscape of UTP. Vermicomposting, where Red Wigglers worms, also known as earthworms are added into the waste has the advantage of speed up the composting process and produce high quality vermicompost than conventional composting method. Humic acid, a known fertilizer which is beneficial for campus landscaping is used by UTP Chem-E-Car team as a fuel source for model cars. Before synthesizing humic acid, vermicompost have to be prepared in different C/N ratio. Optimal C/N ratio is hypothesised for a better voltage generation of vermibattery used in Chem-E-Car. Four composting experiments is conduct with C/N ratio of 20, 25, 30 and 35 respectively.